Pengetahuan kader posyandu dalam pelaksanaan posyandu balita di saat pandemi covid-19 di Kalurahan Seloharjo - Supatmi Supatmi (Health Sciences and Pharmacy Journal, 2021)
Toddler development is very important and must be monitored every month. The appearance of developmental problems in toddlers can be prevented by counseling parents and early detection of toddler development when they come to the posyandu. During the Covid-19 pandemic, everyone is advised to stay at home and reduce contact with other people. On the other hand, monitoring of toddlers is very important to be done. The knowledge of posyandu cadres in implementing posyandu in the pandemic era is very important for cadres' guidelines in carrying out their roles and tasks in monitoring the development of toddlers. The purpose of this study is to describe the knowledge of cadres at the Posyandu Kalurahan Seloharjo about the implementation of Posyandu in the pandemic era. This study used a quantitative descriptive method, with the research sample taking using a total sampling of cadres who are active in the Posyandu Kalurahan Seloharjo. There were 72 respondents. Collecting data used a research instrument in the form of a questionnaire. Data analysis used percentage. The results showed 52 respondents (72%) had good knowledge, 14 respondents (19%) had sufficient knowledge and 6 respondents (8%) had poor knowledge. The knowledge of cadres about the implementation of posyandu during the pandemic is generally good. Knowledge of Posyandu implementation during the Pandemic is expected to monitor the growth and development of toddlers.